Philosophy of Education in Ethical Decision Making in the Classroom - Herlina Herlina; Abdullah Sinring; Ansari Ansari (Departement of Mathematics Education, 2024)
The goal of this study is to provide educators a deeper understanding of how to apply ethical theories in practical classroom settings to help them make morally sound decisions. The author uses a literature study approach. The author carries out the analysis process by exploring the application of various ethical theories developed by prominent philosophers such as Immanuel Kant, John Stuart Mill, and Aristotle in the context of education. Ethical decision-making in the classroom is a key element in education that has a long-term impact on the development of student character. Ethical decisions made by teachers, whether based on deontology, utilitarianism, or virtue ethics, influence a learning environment that is not only fair but also supports the formation of students' morals and character. An educational philosophy that integrates ethical principles provides teachers with a solid foundation in dealing with everyday ethical dilemmas, both in the context of assessment, discipline management, and interactions with students. Therefore, the role of teachers as moral guides is very important in creating an environment that not only prioritizes academic results but also the moral character of students, which will guide them in their social lives (Jones & Brooks, 2020; Smith & Thomas, 2021). In order to create more equitable, inclusive, and humane learning environments, we need to further research on the application of educational philosophy to ethical decision-making in the classroom (Tatum, 2022).